EDUKASI MENCUCI TANGAN ENAM LANGKAH DENGAN BENAR PADA IBU YANG MEMILIKI BALITA UNTUK MENCEGAH TERJADINYA PENYAKIT DIARE: EDUKASI MENCUCI TANGAN ENAM LANGKAH DENGAN BENAR PADA IBU YANG MEMILIKI BALITA UNTUK MENCEGAH TERJADINYA PENYAKIT DIARE DI DESA BANYUMAS TAHUN 2026 - Muhammad Nur Maghribi Sembiring; Leny Suarni; Desi Lianti Sari Hasibuan; Ilham Syahputra Siregar; Muhammad Simba Sembiring (INSTITUT KESEHATAN DELI HUSADA, 2026)
Diarrheal disease remains a significant public health issue among children under five, particularly in developing countries. Poor hand hygiene practices among caregivers, especially mothers, contribute to the transmission of infectious agents. This study aimed to evaluate the effectiveness of health education on the proper six-step handwashing technique among mothers of toddlers in preventing diarrheal diseases. A community-based educational intervention was conducted in Banyumas Village, Langkat Regency, Indonesia, involving 27 mothers of toddlers. The intervention included lectures, demonstrations, and interactive discussions on diarrhea prevention and proper handwashing techniques. Evaluation was conducted through direct observation and participant feedback. The findings indicated an improvement in participants’ knowledge and skills regarding diarrhea prevention and proper six-step handwashing practices. Most participants were able to correctly demonstrate the handwashing technique after the intervention and showed increased awareness of hygiene practices. Health education on proper handwashing techniques effectively improves mothers’ knowledge and skills, which may contribute to reducing the incidence of diarrheal diseases among toddlers. Keywords: Handwashing, Diarrhea prevention, Health education